An Analysis Of Host Factor And Enviroment With The Incidence Of Pulmonary Tuberculosis In The Working Area Of Telaga Dewa Health Center, Bengkulu City - Gustiana, Sika Mana; Darmawansyah, Darmawansyah; Sari, Fikitri Mrya; Rohani, Tuti; Retni, Retni (Journal Hygeia Public Health, 2024)
Intoduction: The World Health Organization (WHO) states that nearly one-quarter of the world's population is infected with the Mycobacterium tuberculosis bacteria, with approximately 89% of tuberculosis cases occurring in adults and 11% in children. Indonesia ranks third globally, with an estimated 9.9 million people suffering from pulmonary TB. In 2023, the Health Office of Bengkulu City reported 686 cases. There were 34 cases of pulmonary TB identified in the Working Area of the Telaga Dewa Health Center in Bengkulu City. The aim of this study is to identify the factors associated with the incidence of pulmonary TB in the Working Area of the Telaga Dewa Health Center in Bengkulu City. Method: The method used is an observational analytic study design with a case-control approach, collecting data through questionnaires distributed to 34 respondents who tested positive for pulmonary TB and 34 respondents who tested negative in the Working Area of the Telaga Dewa Health Center, using Total Sampling technique. Result and Discussion: This study shows that the frequency distribution indicates that the majority of respondents (57.4%) have low knowledge, 52.9% have no history of contact, 44.1% are smokers, 61.8% have inadequate ventilation area, and 72.1% live in adequate housing density. Bivariate analysis results indicate a relationship between knowledge and the incidence of pulmonary TB (P = 0.003), no relationship between contact history and the incidence of pulmonary TB (P = 0.224), a relationship between smoking status and the incidence of pulmonary TB (P = 0.007), a relationship between ventilation area and the incidence of pulmonary TB (P = 0.025), and no relationship between housing density and the incidence of pulmonary TB (P =0.105). Conclusion: community health center staff pay close attention to the complete and clear address data of pulmonary TB patients to facilitate investigations or research on patients with pulmonary TB.